Effect of Genetically Modified Organisms (Gmos) on Health and Environment in Southwestern Nigeria: Scientists' Perception - O I Oladele; O A Akinsorotan (Journal of Agricultural Extension, 2007)
The study was carried out in South Western Nigeria to determine the perception of scientists in Universities and Research Institutes on the effect of GMOs on health and environment. This ispredicatedon the fact that scientists'perception wouldinfluence the on-going debate as a prelude to Nigeria being a signatory to the use of GMOs. Using a simple random sampling technique a total of one hundred and eighty respondents were selected from a population of 760 and then interviewed. Data were collected through the use of a structured questionnaire with a reliability coefficient of 0.92 and analysis was done using frequency counts, percentages andprobit regression model. Scientists were between 31and 40years (59.40%) wereMSCholders (44.44%), got theirinformation on GMOs from journals (89.60%) and were males (56.70%). Majority of the scientists had low awareness of the GMOproducts (52.8%), and lowperception (54.5percent). There was a significant relationship between awareness, age, religion, radio, newspaper, scientific periodicals and their perception toward GMOs. There was no significant difference in perception, and awareness between scientists in Universities andresearch institutes.